2011
DOI: 10.3758/s13414-011-0235-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and visuospatial working memory tests predict performance in classic multiple-object tracking in young adults, but nonspatial measures of the executive do not

Abstract: An individual-differences approach was used to investigate the roles of visuospatial working memory and the executive in multiple-object tracking. The Corsi Blocks and Visual Patterns Tests were used to assess visuospatial working memory. Two relatively nonspatial measures of the executive were used: operation span (OSPAN) and reading span (RSPAN). For purposes of comparison, the digit span test was also included (a measure not expected to correlate with tracking). The tests predicted substantial amounts of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…A significant correlation was also observed between performance on the visual attention and auditory working memory tasks. This result is interesting in light of literature on the working memory demands of the multiple object tracking task (e.g., [ 63 ]) and suggestive of visuospatial memory demands of the digit span backwards task [ 64 ]. Several studies have shown the role of visuospatial resources in the backwards digit span task, both behaviorally (e.g., [ 65 ]) and with evidence from neuroimaging (e.g., [ 66 ]).…”
Section: Discussionmentioning
confidence: 70%
“…A significant correlation was also observed between performance on the visual attention and auditory working memory tasks. This result is interesting in light of literature on the working memory demands of the multiple object tracking task (e.g., [ 63 ]) and suggestive of visuospatial memory demands of the digit span backwards task [ 64 ]. Several studies have shown the role of visuospatial resources in the backwards digit span task, both behaviorally (e.g., [ 65 ]) and with evidence from neuroimaging (e.g., [ 66 ]).…”
Section: Discussionmentioning
confidence: 70%
“…Previous research has shown that tracking capacity during MOT is directly related to spatial working memory capacity in typical adults (Allen et al 2006; Cavanagh and Alvarez 2005), predicting much of the individual variability in MOT capacity (Trick et al 2012). As working memory deficits have been reported in autism for static displays (Bennetto et al 1996; Lopez et al 2005; Luna et al 2007; Poirier et al 2011; Russo et al 2007), though see (Griffith et al 1999; Ozonoff and Strayer 2001; Russell et al 1996) it certainly seems possible that deficits in working memory capacity in ASD could at least partially explain the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Listening and vocalizing did not affect performance; it was the act of preparing a vocal response that was harmful. MOT measures sustained attention over time, depending on visuospatial working memory (Trick, Mutreja, & Hunt, ) and other processes; however, the role that selective spatial attention plays in this complex task is unknown. Importantly, MOT does not typically require the deployment of attention across a wide field of view.…”
mentioning
confidence: 99%